Дидактична гра як спосіб формування толерантності молодших школярів в умовах інклюзії - Кайдалова, Галина; Kaidalova, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглядається проблема використання дидактичної гри у навчально-виховному процесі молодших школярів з метою формування моральних якостей, серед яких особлива увага приділяється поняттю толерантності. Наголошується на важливості виховання норм толерантної поведінки з моменту приходу дитини до школи, що здатне вплинути та поступово змінювати сучасне суспільство. Охарактеризовано особливості, структурні елементи, етапи і вимоги, що встановлюються до дидактичної гри. Зазначено, що дидактична гра в умовах інклюзивної освіти здатна вирішити ряд проблем, серед яких як налаштування стосунків між учнями, зменшення або й знищення бар’єру спілкування, так і можливість проявити себе нарівні з іншими, гарна спроба згуртуватися у міцний класний колектив. Обґрунтовано здатність дидактичної гри здійснювати позитивний виховний вплив у дусі толерантності на свідомість молодших школярів. The article examines the problem of using didactic game in the educational process of primary school children with purpose to form moral qualities; special attention is paid on the concept of tolerance. Didactic game is a collective or individual activity, in which children get training tasks as gaming task that is caused and controlled by gaming regulations. The purpose of didactic games is to form pupil's ability to combine theoretical knowledge with practical activities. The usage of didactic game in the teaching pupils of primary school serves like good activization in the conditions of inclusive education. Its preparation and realization needs from teacher some time consuming, planning, implementation and results of the pre-set training and upbringing tasks that the game can satisfy and fulfill. Children with special needs, being full schoolboy or schoolgirl, do not require teachers excessive care and during the game he or she are the same game's member like all others pupils. If game is well organized it can solve a number of problems, which include: setting good relations between pupils, reduce or destroy the barrier of communication, the ability to display themselves on a par with other, good attempt to unite the class group into one strong team. In modern society, where, along with humanity there is violence, very important role plays such category of moral upbringing as tolerance. Educating children according to the norms of tolerance is extremely important. They must understand that everyone – are unique personality; all people depend or complement each other, which makes it possible to identify some common or distinctive features of their existence; like everyone has the right for life, such everyone has the right on respecting their own human dignity and understanding from others.
Didactic Game as a Way of the Formation of Tolerance in Junior Pupils in Terms of Inclusion
Keywords: дидактична гра; молодші школярі; толерантність; інклюзивна освіта; виховання; навчання; didactic game; junior pupils; tolerance; inclusive education; upbringing; training